Policy Without Delivery: Administrative Coordination and Development Outcomes in Nigeria’s Multisector Development Plans, 2021–2025 - Uchola Kenedya; Efebo Belinda God’swill Efereboa; Victor Prince Charlesa (Dynamics of Politics and Democracy, 2026)
Purpose: This study examines how digital transformation influences the strategic capability of deposit money banks in Rivers State, Nigeria, particularly in light of persistent operational challenges despite significant digital investments. Research Methodology: A survey research design was adopted. Data were collected from 91 managers and heads of departments across 15 deposit money banks using a proportionate sampling technique. The Pearson Product Moment Correlation Coefficient was employed to analyze the relationships between digital transformation variables and dimensions of strategic capability. Results: The findings reveal that digital strategy and digital customer experience positively and significantly correlate with the three dimensions of strategic capability—strategic sensing, strategic seizing, and strategic reconfiguring (p < 0.01). This indicates that well-implemented digital transformation initiatives strengthen banks’ dynamic capabilities. Conclusions: Digital transformation, when strategically aligned and customer-focused, enhances banks’ ability to sense opportunities, seize market advantages, and reconfigure resources effectively, thereby improving long-term competitiveness in a dynamic financial environment. Limitations: The study is limited to deposit money banks in Rivers State and relies on cross-sectional survey data, which may limit generalizability and causal inference. Contributions: This study contributes empirical evidence on the linkage between digital transformation and dynamic strategic capabilities in the Nigerian banking sector. It offers practical insights for bank executives to institutionalize clear digital strategies and continuously improve digital customer experience to achieve sustainable competitive advantage.